Co-design of eHealth Interventions With Children and Young People - Thabrew, Hiran; Fleming, Theresa; Hetrick, Sarah; Merry, Sally (Frontiers in Psychiatry, 2018)
Co-design can lead to the development of interventions that are more engaging, satisfying and useful to potential users. However, using this methodology within the research arena requires a shift from traditional practice. Co-design of eHealth interventions with children and young people has additional challenges. This review summarises the applied core principles of co-design and recommends techniques for undertaking co-design with children and young people. Three examples of co-design during the development of eHealth interventions (Starship Rescue, a computer game for treating anxiety in children with long-term physical conditions, a self-monitoring app for use during treatment of depression in young people, and HABITS, the development of an emotional health and substance use app and eHealth platform for young people) are provided to illustrate the value and challenges of this contemporary process.